Evolution of microstructure and deformation mechanisms in a metastable Fe42Mn28Co10Cr15Si5 high entropy alloy - Shen, Jiajia (2024)
JS, JGL and JPO acknowledge Fundação para a Ciência e a Tecnologia (FCT - MCTES) for its financial support via the project UID/00667/2020 (UNIDEMI). JS acknowledges the China Scholarship Council for funding the Ph.D. grant (CSC NO. 201808320394). ZZ acknowledges Science and Technology Project of Sichuan Province (2020ZDZX0015). The authors acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Beamtime was allocated for proposal I-20210899 EC. Publisher Copyright: © 2024 The Author(s)